Bioengineered Zinc Oxide Nanoparticle-Loaded Hydrogel for Combinative Treatment of Spinal Cord Transection - Lin, Sen; Zhao, Hao-sen; Xu, Chang; Zhou, Zi-peng; Wang, Da-hao; Chen, Shu-rui; Mei, Xi-fan (Frontiers in Bioengineering and Biotechnology, 2022)
Spinal cord injury (SCI) is one of the most destructive diseases. The complex hyperinflammation microenvironment desires complete alleviation. Zinc oxide nanoparticles (ZnONPs) have been widely reported to have low cell toxicity and satisfying anti-inflammation function. Furthermore, green synthesis procedures can improve the capabilitiy of ZnONPs and develop possible utilization in the treatments of disorders. However, the efficient administration and underlying mechanism of ZnONPs after SCI remains hazy. Herein, an innovative approach is built by utilizing ZnONPs loaded in a skeletal muscle-derived adhesive hydrogel (ZnONPs-Gel). Different from systemic application of ZnONPs, local administration of the ZnONPs-Gel offered the ZnONPs-loaded extracellular matrix with beneficial biocompatibility to the injured spinal cord, thereby promoting effective remission of hyperinflammation microenvironment after SCI. The ZnONPs-Gel significantly improved function recovery by downregulating neuroinflammation and reactive oxidative stress (ROS). The therapy based on local administration of the ZnONPs-Gel showed a novel immunomodulatory approach for potent treatment of SCI.